Immune Infiltration in Invasive Lobular Breast Cancer. (20th February 2018) - Desmedt, Christine; Salgado, Roberto; Fornili, Marco; Pruneri, Giancarlo; Van den Eynden, Gert; Zoppoli, Gabriele; Rothé, Françoise; Buisseret, Laurence; Garaud, Soizic; Willard-Gallo, Karen; Brown, David; Bareche, Yacine; et al.
Abstract: Background: Invasive lobular breast cancer (ILC) is the second most common histological subtype of breast cancer after invasive ductal cancer (IDC). Here, we aimed at evaluating the prevalence, levels, and composition of tumor-infiltrating lymphocytes (TILs) and their association with clinico-pathological and outcome variables in ILC, and to compare them with IDC. Methods: We considered two patient series with TIL data: a multicentric retrospective series (n = 614) and the BIG 02-98 study (n = 149 ILC and 807 IDC). We compared immune subsets identified by immuno-histochemistry in the ILC (n = 159) and IDC (n = 468) patients from the Nottingham series, as well as the CIBERSORT immune profiling of the ILC (n = 98) and IDC (n = 388) METABRIC and The Cancer Genome Atlas patients. All ILC/IDC comparisons were done in estrogen receptor (ER)–positive/human epidermal growth factor receptor 2 (HER2)–negative tumors. All statistical tests were two-sided. Results: TIL levels were statistically significantly lower in ILC compared with IDC (fold-change = 0.79, 95% confidence interval = 0.70 to 0.88, P < .001). In ILC, high TIL levels were associated with young age, lymph node involvement, and high proliferative tumors. In the univariate analysis, high TIL levels were associated with worse prognosis in the retrospective and BIG 02-98 lobular series, although they did not reach statistical significance in the latter. The Nottingham series revealed that the levels of intratumoral but not total CD8 + were statistically significantly lower in ILC compared with IDC. Comparison of the CIBERSORT profiles highlighted statistically significant differences in terms of immune composition. Conclusions: This study shows differences between the immune infiltrates of ER-positive/HER2-negative ILC and IDC in terms of prevalence, levels, localization, composition, and clinical associations.